“When the hell are you going to grow up?”: a life-course account of hybrid masculinities among incarcerated men - Umamaheswar, Janani (Journal of Developmental and Life-Course Criminology, 2020)
Purpose: Recent life-course scholarship has argued that desistance from (rather than persistence in) crime is a marker of adulthood. In this article, I argue that a commitment to desistance is only one of many elements of the participants’ sense of adult masculinity, which is best understood by drawing on theoretical literature on “hybrid masculinities.” By linking life-course criminological literature with recent theoretical advancements in the sociology of gender, I connect two important, but as yet independent, strands of research. Methods: Using the grounded theory approach to qualitative research, I performed inductive analyses of 24 in-depth interviews with adult men incarcerated at a state-run facility in the Northeastern USA. Results: I argue that the participants construct hybrid masculinities that combine conventionally masculine traits (such as being a provider and protector) with conventionally feminine traits (such as loyalty, humility, and emotional expressiveness). These hybrid masculinities manifest through the participants’ reliance on intangible markers of adulthood, and they emerge gradually over the men’s life course. I further argue that the disruptions that incarceration poses to the men’s life course impede their ability to realize their hybrid masculinities fully. Conclusion: The current research contributes to the burgeoning literature that attempts to correct the oversimplified portrayal of incarcerated men as singularly hypermasculine, and it also highlights how incarceration disrupts men’s life course, making it difficult for them to be the “hybrid” men that they wish to be. © 2020, Springer Nature Switzerland AG.
Keywords: Hybrid masculinity; Incarceration; Masculinity; Prison; The life course; dept.soc; peer-reviewed